2014
DOI: 10.1103/physrevlett.113.258302
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Glass Singularities and Isodynamics in a Core-Softened Model for Glass-Forming Systems

Abstract: We investigate the slow dynamics of a simple glass former whose interaction potential is the sum of a hard core and a square shoulder repulsion. According to mode coupling theory, the competition between the two repulsive length scales gives rise to a complex dynamic scenario: besides the fluid-glass line, the theory predicts a glass-glass line in the temperature-packing fraction plane with two end points. Interestingly, for critical values of the square-shoulder parameters, such end points can be accessed fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Previous works have shown that one can estimate the locus of the glass transition by monitoring the so-called isodiffusivity (iso-D) lines [77][78][79], along which D remains constant. Importantly, it has been shown that the iso-D lines always maintain, for not too large values of the probed D, the same shape as the ultimate line of arrest.…”
Section: Multiparticle Dynamical Responsementioning
confidence: 99%
“…Previous works have shown that one can estimate the locus of the glass transition by monitoring the so-called isodiffusivity (iso-D) lines [77][78][79], along which D remains constant. Importantly, it has been shown that the iso-D lines always maintain, for not too large values of the probed D, the same shape as the ultimate line of arrest.…”
Section: Multiparticle Dynamical Responsementioning
confidence: 99%
“…The structural relaxation of dense liquids exceeds microscopic time scales by orders of magnitude upon approaching the glass transition via compression or cooling the system. The origin of the glass transition remains heavily debated [1][2][3][4][5][6][7][8][9][10][11][12][13][14] and still constitutes a challenge for theory, simulation, and laboratory experiments, although many facets of the phenomena associated with the glass transition have been rationalized successfully within the mode-coupling theory of the glass transition [15][16][17][18][19] developed during the last thirty years.…”
Section: Introductionmentioning
confidence: 99%
“…Typical of an approach to a glass, the mean square displacement (MSD) averaged over all the passive particles shows a plateauing and cage hopping dynamics, as the density φ is increased (Fig. S1) [30,[39][40][41]. From these graphs we extract the long time diffusivity D ∞ (Supplementary Information Sec.…”
Section: Interplay Between Active Self-propulsion and Viscoelasticitymentioning
confidence: 99%